INCIDENCE AND CLINICAL PICTURE OF UPPER RESPIRATORY INFECTION IN CHILDREN RECEIVING ZINC SUPPLEMENT - Widagdo, Widagdo (Jurnal Kedokteran YARSI, 2007)
The National Household Health Survey (1995) reported that the prevalence of upper respiratory infection (URI) in Indonesia was found 25.3% for all ages and 47.1% for the under five children. Reports of studies on the effect of zinc in the reduction of respiratory infection stated inconsistentresults. The objective of this community base study is to evaluate the effect of zinc as the attempt to reduce the incidence of URI. We have studied the effect of daily supplementation of 10 mg elemental zinc in a double blind, randomized, controlled trial consisting of 37 children (zinc group) and 36 children (control group) of 6 months - 5 years old. The distribution of preparation and monitoring of morbidity were performed regularly once a week along 2-month study period. During the 2-month study (February-April 2001) we found 24 URI cases in the zinc group and 24 cases in the control group. Time series analysis concerning the incidence and severity of the zinc group showed a negative slope (Yt: a ? bx), while the placebo group showed a positive slope (Yt: a + bx). The evidence and severity of URI in zinc groups within the 1st and 2nd months showedsignificant different, while it was not in the control group. The study obviously showed the benefit of zinc supplementation in the reduction of URI as showed by negative slope in the time series analysis, and significant decreased of the incidence and the severity of URI in zinc group. There was no side effect of zinc supplemented noted. We suggest, therefore regular zinc supplementation to the diet of the children in the low economic level community are needed.